2014
DOI: 10.1016/j.semcancer.2014.04.009
|View full text |Cite
|
Sign up to set email alerts
|

Sorting it out: Regulation of exosome loading

Abstract: Extracellular vesicles (EVs), a term that includes both exosomes of endocytic origin and vesicles derived from plasma membranes, are continuously secreted by cells to the extracellular environment, and represent a novel vehicle for cell-cell communication. Exosomes contain specific repertoires of proteins and RNAs, indicating the existence of mechanisms that control the sorting of molecules into them. Although the molecular mechanisms that regulate the loading of proteins into exosomes have been studied for ye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
548
0
13

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 631 publications
(574 citation statements)
references
References 140 publications
13
548
0
13
Order By: Relevance
“…For example, the presence of Tyrosine-protein kinase Fer as one of the most abundant EV proteins and second only to CD63 (Table 2) suggests kinase activity within SF EVs, while the presence of Ubiquitin-60S ribosomal protein L40 supports reported roles for ubiquitin in protein trafficking to exosomes [4143]. Unexpectedly, the Membrane Attack Complex components, Complement C9 and C8α, were also identified, suggesting EVs may be involved in facilitating complement-mediated immune responses in RA SF.…”
Section: Discussionmentioning
confidence: 90%
“…For example, the presence of Tyrosine-protein kinase Fer as one of the most abundant EV proteins and second only to CD63 (Table 2) suggests kinase activity within SF EVs, while the presence of Ubiquitin-60S ribosomal protein L40 supports reported roles for ubiquitin in protein trafficking to exosomes [4143]. Unexpectedly, the Membrane Attack Complex components, Complement C9 and C8α, were also identified, suggesting EVs may be involved in facilitating complement-mediated immune responses in RA SF.…”
Section: Discussionmentioning
confidence: 90%
“…For example, exosomes derived from the same cells were long thought to be similar in their protein, nucleic acid, and lipid compositions, but recent reports have shown that exosomes originating from the same parental cells can have different molecular compositions [145147]. This heterogeneity occurs because the biogenesis of MVB and sorting of components to intraluminal vesicles require both the transport (ESCRT)-dependent and -independent pathways [59,60,148]. …”
Section: Limitations and Factors That Should Be Overcome For The Thermentioning
confidence: 99%
“…The fulcrum of this review is that PTMs can direct exosome loading. Exosomes do not mirror the protein composition of their parental cells, and some proteins appear enriched in exosomes by selective mechanisms of protein cargo sorting controlled by specific PTMs [18]. The main PTMs are summarized in Table 1.…”
Section: Post-translational Modificationsmentioning
confidence: 99%